Application of Quality Control and Risk Management in Maintaining Product Quality with A Risk Breakdown Structure Approach - Alvina Alvina (Jurnal Riset Ilmu Teknik, 2023)
This research was conducted in a company that operates in the printing or graphics sector. The concept of quality control is the most critical part because newspapers or printed media are products with the fastest production process. PT carries out the quality control process. PT XYZ to lower the failed results on the paper. Quality control measurements use the P chart method. Results of quality control measurements at PT. XYZ is outside the control limits, and that is not normal, so corrective action is needed, especially the number of failed newspapers. On average, newspapers failed from January to May, reaching 8.24% of the total newspapers produced. Events that cause failure in newspapers are analyzed through risk management. Risk management measurements use the Risk Breakdown Structure (RBS) and Fault Tree Analysis (FTA) methods. Risk management results show that five risks cause newspaper failure, namely scattered ink, slanted fonts, blurred images, dirty images, and thick fonts.